Оцінка рівня інвестиційного забезпечення розвитку підприємств агарного сектору - Жадан В. С. (My University, 2018)
UK: Проаналізовано обсяг та динаміку капітальних інвестицій у сільське господарство України; визначено структуру джерел фінансування капітальних інвестицій; обґрунтовано роль банківського кредиту у фінансуванні інвестиційного розвитку підприємств аграрної галузі; проаналізовано основні програми кредитування, у тому числі й пільгові інвестиційні кредити. EN: The problem of investment support for the development of enterprises in the agrarian sector is extremely relevant in recent years. According to the State Statistics Service of Ukraine, the total volume of capital investments in the agrarian sector of the economy in January-December 2017 amounted to UAH 57.8 billion. It is 12.8 billion UAH. or 28.3% more, compared to the same period of the previous year. The main source of financing of capital investments remains the own funds of enterprises and organizations. With regard to bank loans, this source is still less affordable for capital investment. Today, among the programs of lending to the agrarian enterprises, in our opinion, the most interesting are lending programs from the Republic of Belarus and the program of financing of the German-Ukrainian Fund. The advantages of the lending programs above are: affordable cost of credit resources; reliable financing of business needs; lending to agribusinesses; adapted loan / credit line repayment schedule; an individual approach to each client; quick decision making on a loan. The volume of bank lending to agricultural enterprises largely depends on the level of state support. Starting in 2015, a program of state financial support for agricultural enterprises was restored in Ukraine through the mechanism of cheapening of loans and compensation of lease payments.
Еvaluation of the level of investment provider of development of agricultural sector enterprises
Keywords: капітальні інвестиції; джерела фінансування; обсяг вкладень; програми кредитування; пільгові кредити; державна підтримка; capital investments; sources of financing of capital investments; volume of credit investments; programs of crediting enterprises of agrarian sector; preferential loans; state support